HUBUNGAN SIT TO STAND ABILITY TERHADAP GAIT SPEED PADA LANSIA - Hasna Nabila, Farras; Kusumawati, Yoni Rustiana; Rustanti, Marti (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: In the elderly there is an aging process which results in changes in body systems, one of which is the musculoskeletal system which results in a decrease in functional ability. A person’s can be measured using sit to stand ability and gait speed as an objective measure of functional mobility to predict functional decline. Objective: To determine the relationship between sit to stand ability and gait speed in the elderly. Design: Quantitative observational descriptive. Subjects: Elderly Posyandu Melati 3, Tegalrejo Village, Ceper District, Klaten Regency, as many as 37 people who met the inclusion criteria were made into one group and measured sit to stand ability using the 5 Times Sit To Stand Test and gait speed was measured using the 10 Meter Walking Test at one time . Results: The normality test using the Shapiro-Wilk test showed normal results of p=0.134 for sit to stand ability and p= 0.784 for gait speed. Correlation test found a relationship with r = 0.706. Conclusion: There is a strong negative relationship between sit to stand ability and gait speed in the elderly.